2014
DOI: 10.3389/fnana.2014.00158
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of Notch-dependent neurogenic markers in the chick embryonic nervous system

Abstract: The establishment of a functional nervous system requires a highly orchestrated process of neural proliferation and differentiation. The evolutionary conserved Notch signaling pathway is a key regulator of this process, regulating basic helix-loop-helix (bHLH) transcriptional repressors and proneural genes. However, little is known about downstream Notch targets and subsequently genes required for neuronal specification. In this report, the expression pattern of Transgelin 3 (Tagln3), Chromogranin A (Chga) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…The conservation of gene expression was analysed by comparison with chick data (Table 2). Similar to the expression patterns observed in the chick embryo [44], these neuronal markers were differentially expressed throughout the early neuronal populations in the brain (Fig. 1 and Table 2), cranial ganglia and spinal cord (data not shown) in the developing mouse embryo.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The conservation of gene expression was analysed by comparison with chick data (Table 2). Similar to the expression patterns observed in the chick embryo [44], these neuronal markers were differentially expressed throughout the early neuronal populations in the brain (Fig. 1 and Table 2), cranial ganglia and spinal cord (data not shown) in the developing mouse embryo.…”
Section: Resultssupporting
confidence: 82%
“…Recently, a number of neuronal markers, described as part of the Notch/proneural network, were shown to be specifically expressed in the early neuronal populations of the chick brain [44]. To investigate the role of this network during formation of these neuronal populations in the developing mouse brain, the expression patterns of those markers, Nhlh1 , Tagln3 , Chga , Cntn2 and Stmn2 were analysed between E8.5 and E10.5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found the MAML2 promoter became hypermethylated in senescent mesenchymal stem cells after long term culture. 64 We found another Notch related gene, the actin-binding protein involved in cytoskeletal organization, 65 TAGLN3, demethylated in activated NK cells.…”
Section: Novel Methylation Sites In Signaling Pathways: Maml2 Tagln3mentioning
confidence: 99%